To compare the effectiveness of constraint induced movement therapy versus motor relearning programme to improve motor function of hemiplegic upper extremity after stroke - Batool, Sana (Pak J Med Sci, 2015)
OBJECTIVE: To compare the effectiveness of constraint induced movement therapy versus motor relearning programme to improve motor function of hemiplegic upper extremity after stroke. METHOD: A sample of 42 patients was recruited from the Physiotherapy Department of IPM&R and Neurology OPD of Civil Hospital Karachi through non probability purposive sampling technique. Twenty one patients were placed to each experimental and control groups. Experimental group was treated with Constraint Induced Movement Therapy (CIMT) and control group was treated with motor relearning programme (MRP) for three consecutive weeks. Pre and post treatment measurements were determined by upper arm section of Motor Assessment Scale (MAS) and Self Care item of Functional Independence Measure (FIM) Scale. RESULTS: Intra group analysis showed statistically significant results (p-value<0.05) in all items of MAS in both groups. However, advanced hand activities item of MAS in MRP group showed insignificant result (p-value=0.059). Self-care items of FIM Scale also showed significant result (p-value< 0.05) in both groups except dressing upper body item (p-value=0.059) in CIMT group and grooming and dressing upper body items (p-value=0.059 & 0.063) in MRP group showed insignificant p-values. CONCLUSION: CIMT group showed more significant improvement in motor function and self-care performance of hemiplegic upper extremity as compared to MRP group in patients with sub-acute stroke assessed by the MAS and FIM scales. Thus CIMT is proved to be more statistically significant and clinically effective intervention in comparison to motor relearning programme among the patients aged between 35-60 years. Further studies are needed to evaluate CIMT effects in acute and chronic post stroke population.